Cover Feature: K+ Transport in Perfluorosulfonic Acid Membranes and Its Influence on Membrane Resistance in CO2 Electrolysis (ChemElectroChem 4/2022). Issue 4 (11th January 2022) - Vetter, Kim‐Marie; Härtl, Jamie; Reinisch, David; Reichbauer, Thomas; Martić, Nemanja; Hinrichsen, Kai‐Olaf; Schmid, Günter
Abstract : The Cover Feature illustrates a study where a PEM water electrolysis model setup was used to quantify the increase in membrane resistance and cell voltage when K + ‐based electrolytes are used in combination with a PFSA membrane. Potassium cations are soaked into a PFSA membrane against the electroduffusion direction and occupy sulfonate groups thus blocking proton transport channels. The study provides important insights about energy contributions in CO2 electrolysis applications. More information can be found in the Article by K.‐M. Vetter et al.